Wicked. Part I [videorecording (DVD)] - Holzman, Winnie; Fox, Dana; Schwartz, Stephen; Schwartz, Stephen; Powell, John, 1963-; Erivo, Cynthia, 1987-; Grande, Ariana; Bailey, Jonathan, 1988-; Slater, Ethan, 1992-; Yang, Bowen, 1990-; Bode, Marissa, 2000-; Yeoh, Michelle, 1962-; et al. (Universal, 2025)
Wicked, the untold story of the witches of Oz, a young woman, misunderstood because of her unusual green skin, who has yet to discover her true power, and Glinda, a popular young woman, gilded by privilege and ambition, who has yet to discover her true heart. The two meet as students at Shiz University in the fantastical Land of Oz and forge an unlikely but profound friendship. Following an encounter with The Wonderful Wizard of Oz, their friendship reaches a crossroads, and their lives take very different paths. Glinda's unflinching desire for popularity sees her seduced by power, while Elphaba's determination to remain true to herself, and to those around her, will have unexpected and shocking consequences for her future. Their extraordinary adventures in Oz will ultimately see them fulfill their destinies as Glinda the Good and the Wicked Witch of the West.